2021
DOI: 10.1097/mao.0000000000003194
|View full text |Cite
|
Sign up to set email alerts
|

Central Processing in Tinnitus: fMRI Study Outlining Patterns of Activation Using an Auditory Discrimination Task in Normal Versus Tinnitus Patients

Abstract: Objective:Elucidate brain activity differences between patients with tinnitus and controls.Study Design:Cross-sectional cohort study.Setting:Outpatient Otolaryngology clinic.Patients:Three cohorts; 8 controls, 12 with subjective idiopathic tinnitus (tinnitus without hearing loss), and 12 with both tinnitus and hearing loss.Intervention:An auditory oddball identification task was performed in fMRI scanner.Main Outcome Measures:Task performance and Tinnitus Handicap Inventory (THI) scores were recorded. Brain ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 66 publications
2
19
0
Order By: Relevance
“…Gray matter atrophy gradually spread from the basal ganglia to the angular gyrus, temporal regions, and eventually to the subcortical-cortical network as neurological disease progresses. The angular gyrus was key AD-risk region ( Browndyke et al, 2021 ; Zenke et al, 2021 ). The calcarine sulcus was located posterior to the medial surface of the hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Gray matter atrophy gradually spread from the basal ganglia to the angular gyrus, temporal regions, and eventually to the subcortical-cortical network as neurological disease progresses. The angular gyrus was key AD-risk region ( Browndyke et al, 2021 ; Zenke et al, 2021 ). The calcarine sulcus was located posterior to the medial surface of the hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…Atrophy of the flocculus on the surgical side has been suggested to modulate tinnitus [ 15 , 16 ]. Functional MRI revealed that tinnitus is associated with activities of the Heschl’s gyrus, angular gyrus, cerebellar, and limbic system [ 17 ]. Arachnoid cysts are a benign malformation of the arachnoid layer of the meninges.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 and Figure 3 show the frequency distribution of functional brain regions reported among the studies; 13 studies assessed the auditory cortex, of which 7 showed higher activation in the tinnitus group than controls, 21,23,25,30,35,37,38 while the remaining 6 showed no significantly higher activation. 27,29,31,32,34,36 The inferior colliculus (IC) was assessed in 10 studies, displaying greater activation in tinnitus patients than controls in 7 studies, 24,27,29,30,34,35,38 lower activation in 1 study, 22 and no difference in 2 studies.…”
Section: Roimentioning
confidence: 99%
“…42 Supporting this theory, Zenke et al observed an increased auditory cortex activation. 37 The authors suggest that a limbic-auditory interaction may be to blame for the presence of tinnitus. This study also implied that the primary auditory centers may experience asymmetries in metabolic activity that lead to downstream effects in tinnitus subjects.…”
Section: Auditory Cortex (Figure 4)mentioning
confidence: 99%